Optimasi Sediaan Serum Antiaging Ekstrak Etanol Rambut Baby Corn (Zea mays L.) - Dwi Septyani, Vika Rizky; Wicahyo , Septian Maulid; Raharjo , Danang (Journal of Pharmaceutical and Sciences, 2024)
Skin is one of the organs that serve to protect the body from external influences. Exposure to free radicals causes skin damage, so antioxidant compounds are needed. Baby corn (Zea mays L.) hair contains flavonoids that have the potential to be antioxidants so that they can be formulated into an optimum serum preparation. This experimental study aims to determine the optimal formula concentration and antioxidant activity of anti-aging serum preparation of ethanol extract of Hair (Zea Mays L.). The optimum formula was obtained from the data analysis of Design Expert 13 Simplex Lattice Design method with variations in the concentration of Karbopol and TEA. The results showed that the variation of Karbopol and TEA concentrations affected the physical quality evaluation. The desirability value was 0.903, and the optimum formula concentration was obtained at Karbopol 1.7795% and TEA I2.294%. Data analysis of the optimum formula using the Shapiro-Wilk Normality Test and One Sample T-Test Test resulted in normally distributed data and no significant difference with the predicted value. The antioxidant activity test result of the optimum formula was 65.08 μg/ml with a strong category.